Christ as Chrism, Christ Given Away. (September 2014) - Mercedes, Anna
Abstract This article develops the concept of Christ not as static body but as chrism for bodies. Christ as chrism travels in the matrix of relationality, on a vector toward the benefit of others. Conceptualizing christ as chrism potentially avoids both exclusionary and colonizing tendencies in Christian polity, and frames a Christian ethics that, while vulnerable and risky, marks the sanctity of the one giving Christ away.